2018
DOI: 10.1053/j.sult.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Imaging in Acute Ischemic Stroke

Abstract: Rapid multimodal imaging is essential in the workup and management of acute ischemic stroke. Early parenchymal findings on noncontrast computed tomography or standard magnetic resonance imaging are used to triage patients for intravenous thrombolysis and to provide insight on prognosis. In the wake of recent endovascular stroke trials, advanced techniques including perfusion imaging and noninvasive vascular imaging are becoming important tools to guide potential endovascular treatment or expand therapy windows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…With the development of radiological technology, neuroimaging plays increasingly important roles in the diagnosis and treatment of central nervous system diseases (15). We previously demonstrated that tiro ban was effective and safe in AIS patients who were not undergoing early recanalization treatments.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of radiological technology, neuroimaging plays increasingly important roles in the diagnosis and treatment of central nervous system diseases (15). We previously demonstrated that tiro ban was effective and safe in AIS patients who were not undergoing early recanalization treatments.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the diagnosis of ischemic stroke relies on both clinical assessment (serum biomarkers) and neuroimaging (computed tomography) [22][23][24]. Blood tests can identify multiple biomarkers of ischemic stroke, including proteins involved in inflammation responses, such as C-reactive…”
Section: Diagnosis and Biomarkers Of Ischemic Strokementioning
confidence: 99%
“…Selain sebagai alat diagnostik, pemeriksaan radiologi berperan, serta digunakan sebagai dasar tatalaksana. 6 Pemeriksaan radiologi merupakan pemeriksaan terbaik untuk membedakan stroke iskemik dan hemoragik, juga salah satu faktor penentu kontraindikasi tindakan trombolisis intravena serta menjadi salah satu kriteria tindakan trombektomi mekanik. 2,7 Pemeriksaan MRI dengan DWI memiliki sensitivitas yang lebih baik dan dapat mendeteksi kasus stroke iskemik akut lebih dini dibandingkan CT Scan non-kontras.…”
Section: Pencitraan Pada Stroke Iskemikunclassified